(untitled) (Nonlinear Studies, 2023)
This study examines the existence and uniqueness results for nonlinear neutral conformable implicit fractional differential [] equations with initial and boundary conditions. The fixed point theory and are used to support our conclusions. Two exemplary examples are given in the concluding section.